Common reasoning in games: a Lewisian analysis of common knowledge of rationality - Cubitt, Robin P.; Sugden, Robert (Cambridge University Press, 2014)
Abstract: We present a new class of models of players’ reasoning in non-cooperative games, inspired by David Lewis’s account of common knowledge. We argue that the models in this class formalise common knowledge of rationality in a way that is distinctive, in virtue of modelling steps of reasoning; and attractive, in virtue of being able to represent coherently common knowledge of any consistent standard of individual decision-theoretic rationality. We contrast our approach with that of Robert Aumann (1987), arguing that the former avoids and diagnoses certain paradoxes to which the latter may give rise when extended in particular ways.